2012
DOI: 10.5117/9789089644022
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Drugs before Rock 'n' Roll : Youth Culture and Masculinity during Holland's Golden Age

Abstract: A m s t e r d a m U n i v e r s i t y P r e s s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This group has been largely ignored, even as interest in education and the specific stage of youth has grown from the sixteenth century onwards (Griffths 1996), and even though sociological, psychological, and historical research has identified the accumulation of human capital in the young as a vital catalyst for social change (Klimsta a.o. 2010;Roberts 2012b;Meeus 2011;Moller 1968). Some attention has been paid to students and the way they operated in the changing contexts of universities, as well as to the enormous expansion of the early modern schooling system (Rüegg 1992(Rüegg -2011Van Miert 2009;Houston 1988;Boekholt & De Booy 1987).…”
mentioning
confidence: 99%
“…This group has been largely ignored, even as interest in education and the specific stage of youth has grown from the sixteenth century onwards (Griffths 1996), and even though sociological, psychological, and historical research has identified the accumulation of human capital in the young as a vital catalyst for social change (Klimsta a.o. 2010;Roberts 2012b;Meeus 2011;Moller 1968). Some attention has been paid to students and the way they operated in the changing contexts of universities, as well as to the enormous expansion of the early modern schooling system (Rüegg 1992(Rüegg -2011Van Miert 2009;Houston 1988;Boekholt & De Booy 1987).…”
mentioning
confidence: 99%